2006
DOI: 10.1016/j.ydbio.2006.02.030
|View full text |Cite
|
Sign up to set email alerts
|

Development of the male germline stem cell niche in Drosophila

Abstract: Stem cells are found in specialized microenvironments, or "niches", which regulate stem cell identity and behavior. The adult testis and ovary in Drosophila contain germline stem cells (GSCs) with well-defined niches, and are excellent models for studying niche development. Here, we investigate the formation of the testis GSC niche, or "hub", during the late stages of embryogenesis. By morphological and molecular criteria, we identify and follow the development of an embryonic hub that forms from a subset of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
236
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 128 publications
(250 citation statements)
references
References 50 publications
11
236
0
Order By: Relevance
“…We hypothesize that their disintegration soon after the onset of metamorphosis is a consequence of a sudden increase in the level of dsx F required to promote the rapid female differentiation and counteract any dsx M present, a level that cannot be reached by these mutant cells that have not fully engaged the Sxl f9 positive feedback loop. In this connection it may be relevant that Le Bras and Van Doren (2006) reported that the gonad's requirements for dsx F and dsx M are qualitatively different during embryonic development than at later stages. We can imagine that a sudden shift in sexual identity during a period of rapid differentiation might be more disruptive than an intersexual orientation held consistently throughout development, such as that imposed by a loss of the dsx or ix genes.…”
Section: Discussionmentioning
confidence: 98%
“…We hypothesize that their disintegration soon after the onset of metamorphosis is a consequence of a sudden increase in the level of dsx F required to promote the rapid female differentiation and counteract any dsx M present, a level that cannot be reached by these mutant cells that have not fully engaged the Sxl f9 positive feedback loop. In this connection it may be relevant that Le Bras and Van Doren (2006) reported that the gonad's requirements for dsx F and dsx M are qualitatively different during embryonic development than at later stages. We can imagine that a sudden shift in sexual identity during a period of rapid differentiation might be more disruptive than an intersexual orientation held consistently throughout development, such as that imposed by a loss of the dsx or ix genes.…”
Section: Discussionmentioning
confidence: 98%
“…Finally, by the end of stage 17, a critical structure that regulates the germline stem cells (GSCs), called the hub, forms from a group of 10-12 anterior SGPs, and this structure persists through adulthood ( Fig. 1; Aboïm, 1945;Gonczy et al, 1992;Hardy et al, 1979;Le Bras and Van Doren, 2006). Within the hub, multiple adhesion proteins are expressed from this point forward, including Fasciclin 3 (Fas3), Drosophila E-cadherin (DEcad) and Drosophila N-cadherin (DN-cad) Le Bras and Van Doren, 2006;Yamashita et al, 2003).…”
Section: Overview Of Gonad Morphogenesismentioning
confidence: 99%
“…1; Aboïm, 1945;Gonczy et al, 1992;Hardy et al, 1979;Le Bras and Van Doren, 2006). Within the hub, multiple adhesion proteins are expressed from this point forward, including Fasciclin 3 (Fas3), Drosophila E-cadherin (DEcad) and Drosophila N-cadherin (DN-cad) Le Bras and Van Doren, 2006;Yamashita et al, 2003). In addition, integrins are required to anchor the hub at the anterior end of the gonad (Tanentzapf et al, 2007).…”
Section: Overview Of Gonad Morphogenesismentioning
confidence: 99%
See 2 more Smart Citations